Variability and correlations of traits related to seedling vigor in two natural populations of Pappophorum vaginatum Buckley - Entio, Lisandro José; Mujica, María de la Merced; Busso, Carlos Alberto; Torres, Yanina Alejandra; Montenegro, Oscar Alberto; Ithurrart, Leticia Soledad; Dosindo Giorgetti, Hugo; Rodríguez, Gustavo Dionisio; Bentivegna, Diego; Brevedan, Roberto Eric; Fernández, Osvaldo Alberto; Baioni, Sandra Sonia; et al. (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2022)
It was evaluated variability and phenotypic correlation in traits related to seedling vigor in two natural populations of P.vaginatum. They were weighted and sowed individually 100 caryopses of each population ("A"; "B"). After 43 days it was determined: lenghts aerial (LA), root (LR), total (LT) and longest adventitious root (Ladv), number of adventitious root (n°adv), of leaves (n°hoj), of senescent leaves (n°sen) and of tillers (n°mac) and dry weight aerial (PSA) and root (PSR). It was calculated total dry weight (PST), PSA/PSR and LA/LR. Variability was analyzed by means of descriptive statistic and t test. It was analyzed correlation among traits and multiple regression of traits on PST. Populations did not differ in PST (p≥0.05). "A" had greater (p≤0.01) PSA/PSR, LA/LR and LA. "B" had higher (p≤0.05) LR, Ladv and PSR. Both populations showed significant and positive correlation of PST with LA, LT, Ladv, n°adv, n°hoj y n°mac. The regression was significant (p≤0.01). The variability found within and between populations implies expectations of response to selection. PST varied only within populations suggesting the convenience of intrapopulation selection. The association found between the traits LA and n°mac and the seedling vigor, should be considered for the genetic improvement of the implantation.